Modulating Sound with Acoustic Metafiber Bundles - Jian-ping Xia (Nature Portfolio, 2017)
Abstract Acoustic metamaterials and metasurfaces provide great flexibility for manipulating sound waves and promise unprecedented functionality, ranging from transformation acoustics, acoustic cloaking, acoustic imaging to acoustic rerouting. However, the design of artificial structures with both broad bandwidth and multifunctionality remains challenging with traditional design approaches. Here we present a design and realization of a broadband acoustic metafiber bundle. Very different from previously reported acoustic metamaterials and metasurfaces, not only the metafiber structure is simple, flexible and tunable, but also the metafiber bundle has the advantages of broad bandwidth, high transmission, no resonance-induced energy loss and unchangeable output wavefront owing to eigenmodes in the passbands of the metafiber. Besides, it could also achieve arbitrary complex modulations of cylindrical and plane acoustic wavefronts. The metafiber bundles realize the exciting multifunctionality of both acoustic metamaterials and metasurfaces in a broad frequency range, which provides diverse routes to design novel acoustic devices with versatile applications.